Risk, resilience, and Shariah-compliance - Cheong, Calvin W. H. * (Elsevier, 2021)
Despite the popularity of Islamic Finance, the effects of Shariah-compliance on non-financial firm operations have never been studied. Shariah-compliance requirements presents unique conditions to examine how firms perform under restricted conditions. This paper seeks to examine the effects of Shariah-compliance on the risk and resilience of non-financial firms. Using a dynamic panel system GMM and a host of firm-specific attributes, and a global sample of 2,160 firms across six geographic regions, the results suggest that Shariah-compliant firms have lower firm risk as measured by total and idiosyncratic risk, and greater firm resilience as measured by the percent deviation from the maximum values of sales, cost of goods sold, operating expenses, and share price. These effects are more profound in the years following the U.S. subprime crisis. Results also show socio-cultural norms to have a moderating effect. Further testing shows firms face stiff penalties for losing their Shariah-compliance status. This paper is the first to study the effects of Shariah-compliance on non-financial firm operations on a global scale. This paper also contributes to the capital structure and corporate governance literature as it provides evidence that suggest resource restraints may be beneficial for a firm. The findings of this paper also provide significant value to firms looking to capitalize on the 1.8 billion-strong Muslim market with further insight on the intricacies of Shariah-compliance.